The effects of the Chinese imports on Brazilian manufacturing workers - Lourenço Senne Paz; Kul Prasad Kapri (Economies, 2019)
This study examines the impacts of imports from China and from the Rest of the World (ROW) on the wages of Brazilian manufacturing workers during 2000–2012. In this period, import penetration in Brazil grew by 25 percent, and the Chinese share of it increased from 3 to 20 percent. Using household survey data that encompass both formal and informal workers, we find that imports from China and from the ROW had different effects on manufacturing skilled and unskilled workers' wages. Both the skilled and unskilled workers were negatively affected by an increase in the Chinese import penetration of intermediate inputs. For skilled workers, the ROW import penetration effect was negative for labor-intensive industries and positive for the other industries, while the Chinese import penetration had a positive effect on skilled workers' wages. For the unskilled workers, we find that those in unskilled-labor intensive industries experienced positive impacts from both China and ROW import penetrations, whereas larger import penetrations reduced the wages for unskilled workers in the other industries.
Keywords: F1; O1; 330; Brazil; China; employment; import penetration; manufacturing; wages